Studi Kelayakan Pembangkit Listrik Tenaga Mikrohidro (PLTMH) pada sungai Arter Desa Hurun Kecamatan Padang Cermin Kabupaten Pesawaran Lampung - Agus Sugiri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2013)
Electricity is very important in human life. In Indonesia,electricity is a basic necessity for society and industry. Electrical energy supply in Indonesia is targeted to use the 5% comes from renewable energy, it has been included in the government regulation No. 3 of 2005. One of the power plants that are potentially is Micro Hydro Power (MHP), which is an implementation of the green energy initiative to encourage renewable energy step. If the MHP potential can be developed, then at least 12,000 MWh or 14% of Indonesia's total energy needs in 2005 are contributed by the MHP.The purpose of this final project: